Evaluation of 10 Years Atherosclerotic Cardiovascular Risk, Vitamin D and Metabolic Profiles in Smokers - Mehrdad Simani; Amir Ghaderi; Iman Saffari; Akram Yazdani; Hasan Rajabi Moghaddam; Elaheh Bagherian (International Journal of Medical Toxicology and Forensic Medicine)
Background: Cardiovascular diseases (CVD) are the primary cause of death and a significant contributor to disability. Atherosclerosis cardiovascular diseases (ASCVD) are responsible for high mortality rates, causing millions of deaths each year. The most important avoidable cause of ASCVD and death is cigarette smoking. This study examined the relationship between 10-year ASCVD in smokers with 25(OH)D and metabolic profiles. Methods: This cross-sectional study was conducted at the Beheshti Hospital in Kashan City, Iran. A total of 144 smokers between the ages of 40 and 75 participated in this study. Addiction and cardiovascular specialists evaluated the patient health questionnaire, and the appropriate tool was used to quantify the 10-year ASCVD risk. Nitric oxide (NO), γ-glutamyl-l-cysteinyl-glycine (GSH), high-sensitivity C-reactive protein (Hs-CRP), triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c), total antioxidant capacity (TAC) and 25(OH)D were determined, too. Results: About 93% of the 144 participants in this study were men and their mean age was 52.6±8.56 years. The average risk of ASCVD was 10.44±8.72%. Patients’ lifetime and 10-year risk for ASCVD was significantly and negatively correlated with blood 25(OH) D, HDL, GSH, NO and TAC (P<0.05) and positively with TG, LDL, Hs-CRP, smoking duration, and number of cigarettes (P<0.05). Additionally, a negative correlation was seen between the amount of 25(OH)D and the amount of time spent smoking (P<0.05). Conclusion: The results of this study showed that with increased levels of vitamin D, HDL cholesterol, NO, glutathione, and TAC, the risk of developing atherosclerotic CVD was reduced over 10 years. Also, the risk of developing ASCVD over the next 10 years increased with increased levels of TC, LDL-c, TG, Hs-CRP levels and duration and amount of smoking and hypertension.